Implementation of Real-Time Swarm Drone Formation Using Firebase and MIT App Inventor with Interpolation-Based Control in Gazebo - Wijaya, Ryan Satria; Soebhakti, Hendawan; Fatekha, Rifqi Amalya; Anggraini, Sarah (Politeknik Negeri Batam, 2026)
This paper presents the implementation of a real-time swarm drone formation control system that leverages Firebase as the communication bridge and MIT App Inventor as the user interface. The simulation is conducted in the Gazebo environment with five quadcopter drones. Formation commands are sent from an Android application to Firebase, then processed by a Python-based ROS node to adjust drone positions. Four primary formations - line, triangle, circle, and star - are implemented, along with a dynamic mode enabling sequential transitions among multiple patterns. The integration of linear interpolation ensures smooth transitions, consistent timing, and stable hovering. Experimental results show an average response delay of 0.4–0.6 seconds and stable altitude at 3.5 meters. This approach demonstrates an intuitive and scalable swarm control method. Future enhancements may include telemetry feedback, Firebase authentication, and PID tuning to optimize control accuracy.